2019
DOI: 10.3389/fpls.2019.00497
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Wild Arachis Dehydrin Under Abiotic and Biotic Stresses

Abstract: Plant dehydrins (DNHs) belong to the LEA (Late Embryogenesis Abundant) protein family and are involved in responses to multiple abiotic stresses. DHNs are classified into five subclasses according to the organization of three conserved motifs (K-; Y-; and S-segments). In the present study, the DHN protein family was characterized by molecular phylogeny, exon/intron organization, protein structure, and tissue-specificity expression in eight Fabaceae species. We identified 20 DHN genes, encompassing three (Y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 84 publications
(130 reference statements)
1
18
0
Order By: Relevance
“…Wild-type (WT) A. thaliana plants (ecotype Columbia; Col-0) were transformed with the GV3101-pPZP-AdGolS3 Agrobacterium strain by the floral dip immersion method 32 . The eGFP-positive and hygromycin-resistant T0 transformants were grown in a controlled growth chamber (21 °C with a 12 h photoperiod and light intensity of 120 µmols.m −2 .s −1 ) to obtain transgenic AdGolS3 overexpressing (OE) lines, as described previously 22 . T1 seeds of each transgenic line obtained by self-pollination of T0 plants were germinated on hygromycin selective medium and T1 plants grown to maturity.…”
mentioning
confidence: 99%
“…Wild-type (WT) A. thaliana plants (ecotype Columbia; Col-0) were transformed with the GV3101-pPZP-AdGolS3 Agrobacterium strain by the floral dip immersion method 32 . The eGFP-positive and hygromycin-resistant T0 transformants were grown in a controlled growth chamber (21 °C with a 12 h photoperiod and light intensity of 120 µmols.m −2 .s −1 ) to obtain transgenic AdGolS3 overexpressing (OE) lines, as described previously 22 . T1 seeds of each transgenic line obtained by self-pollination of T0 plants were germinated on hygromycin selective medium and T1 plants grown to maturity.…”
mentioning
confidence: 99%
“…Similarly, the overexpression of AdDHN1, a SKn-type DHN gene from Arachis duranensis in Arabidopsis lines, was found to show enhanced tolerance to combined abiotic stress factors while increasing susceptibility to the biotrophic root node nematode. This contradictory role of AdDHN1 in response to abiotic and biotic stresses supported the idea that it was associated with the overexpression of DHN in the ABA and JA signaling pathways (Mota et al, 2019). In another study, to understand the function of CaDHN4 isolated from pepper in cold and salt tolerance and sensitivity to ABA, expression of CaDHN4 was reduced using a virusinduced gene silencing and overexpressed in Arabidopsis.…”
Section: Signaling Pathways Involved In Dhns Gene Expressionmentioning
confidence: 83%
“…It is possible that these differences in localization are caused by an undefined sequence element (Graether and Boddington, 2014). Some DHN proteins have been observed to contain less conserved motifs (Φ segments) that are located between the K-segments and rich in glycine and polar amino acids (Campbell and Close, 1997;Graether and Boddington, 2014;Mota et al, 2019). The protein structure of DHNs can be described by the presence of the K-, Y-, and S-segments.…”
Section: The Structure and Properties Of Dhnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable evidence has suggested that LEA proteins are important for tolerance of diverse organisms to abiotic stresses (Battaglia et al 2008, Hundertmark andHincha 2008). Moreover, several lines of evidence proposed involvement of LEA protein in biotic stress responses (Salleh et al 2012, Yang et al 2012, Liu et al 2013, Mota et al 2019.…”
Section: Introductionmentioning
confidence: 99%